Field Isolation and Cultivation of Trypanosomatids from Insects - Lukeš, Julius; Votýpka, Jan (Methods in molecular biology, 2020)
Monoxenous (one host) trypanosomatids from insects and other invertebrates can be introduced into axenic culture relatively easily and efficiently, allowing for their transfer from the field into the laboratory. Here we describe simple methods and alternative cultivation protocols, the wider application of which will allow substantial expansion of trypanosomatids available for research.
Keywords: hmyz; Animals; Parasitology; parazitologie; zvířata; Trypanosomatina; Insecta; axenická kultura; Axenic Culture